(untitled) (Research, Society and Development, 2021)
Pre-eclampsia (PE) is defined as a pregnancy-specific disease associated with the onset of hypertension with a multisystemic or multifactorial character after the 20th week of pregnancy, with high rates of morbidity, mortality and prematurity and is responsible for 10% to 15% of maternal death cases in the world. In this sense, it is necessary to provide assistance to pregnant women as early as possible, ensuring maternal and fetal health in a humanized, comprehensive and quality way. In the meantime, the present work is a literature review and aims to propose a reflection based on the analysis of scientific studies on prenatal care in the management of PE. Nevertheless, it was found that 61.2% of pregnant women do not undergo prenatal care, favoring negative obstetric outcomes such as abortion, eclampsia, hemorrhages, prematurity and placental abruption. Furthermore, several factors are associated with the onset of PE, such as stress, anxiety, feeling of abandonment due to the fact that many women do not have their spouse’s participation in prenatal care, thus hindering their adherence. Thus, it is up to health professionals the role of sensitizing and informing pregnant women about the risks, care, use of medication, food, guidance on consultations, in addition to maintaining direct and active communication throughout the assistance. if necessary, the pregnant woman has a multidisciplinary follow-up during her prenatal care, aiming at a holistic care that meets her nutritional, physical and clinical needs throughout the gestational period.